2012
DOI: 10.1007/s10750-012-1270-2
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Salix fragilis alters benthic invertebrate communities and litter decomposition in northern Patagonian streams

Abstract: Invasion by exotic trees into riparian areas has the potential to impact aquatic systems. We examined the effects of the exotic Salix fragilis (crack willow) on the structure and functioning of small streams in northern Patagonian Andes via a field survey of benthic invertebrates and leaf litter and an in situ experiment. We compared leaf decomposition of the native Ochetophila trinervis (chacay) and S. fragilis in reaches dominated by native vegetation versus reaches dominated by crack willow. We hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 50 publications
1
12
0
5
Order By: Relevance
“…Some studies suggested that invasive species can cause alterations at different levels in the structure and functioning of ecosystems (Ehrenfeld 2010). Moreover, the establishment of exotic riparian plants can alter the exchange of organic material between terrestrial and lotic ecosystems, both changing the quantity (Mineau et al 2011(Mineau et al , 2012 or the quality (B€ arlocher & Graça 2002) of terrestrial litter inputs, leading to alterations in the composition (Serra et al 2013) and density (Lester et al 1994) of benthic assemblages. Many studies have shown that, for instance, the introduction and spread of Eucalyptus globulus plantations in Spain had a strong effect on in-stream terrestrial detritus colonization and degradation (Chauvet et al 1997;Pozo et al 1998;Ferreira et al 2006), while other studies have shown weak influence of exotic species on streams (Braatne et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggested that invasive species can cause alterations at different levels in the structure and functioning of ecosystems (Ehrenfeld 2010). Moreover, the establishment of exotic riparian plants can alter the exchange of organic material between terrestrial and lotic ecosystems, both changing the quantity (Mineau et al 2011(Mineau et al , 2012 or the quality (B€ arlocher & Graça 2002) of terrestrial litter inputs, leading to alterations in the composition (Serra et al 2013) and density (Lester et al 1994) of benthic assemblages. Many studies have shown that, for instance, the introduction and spread of Eucalyptus globulus plantations in Spain had a strong effect on in-stream terrestrial detritus colonization and degradation (Chauvet et al 1997;Pozo et al 1998;Ferreira et al 2006), while other studies have shown weak influence of exotic species on streams (Braatne et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, as a result of direct introduction by humans, hydrological disturbance and natural connectivity of lotic environments, exotic plant species represent an average of more than 20% of plant species of riparian areas (Richardson et al 2007). In fact, this topic is quite complex, as exotic species have little effect on leaf decomposition patterns if their physical and chemical characteristics are similar to the native species (Braatne et al 2007), but differences in decomposition rate tend to emerge where exotics are invasive species with different leaf toughness (Serra et al 2013) or C:N ratio (Royer et al 1999). In general, many studies suggested that the presence of exotic plant species could modify the availability and turnover of benthic leaves, influencing the whole ecosystem efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Shifts from native to exotic trees may alter the quality of leaf litter inputs into water body, thus causing effects on quantity and quality of nutrients (Molinero and Pozo, 2006), biotic communities (Weijers et al, 2009) and ecosystem functioning (Martinez et al, 2013). Several studies have been performed to examine invasive species effects on leaf decomposition rates in aquatic ecosystems by litterbags method, but still have found mixed effects (Swan et al, 2008;Marano et al, 2013;Serra et al, 2013). Variability in leaf litter decomposition rates in aquatic systems may be linked to the direct or indirect effect of leaf litter on the changes of benthic communities composition and activity (Bärlocher and Graça, 2002;Medina-Villar et al, 2015), that highlights the importance of specific studies in order to understand the effects of invasions on ecosystem functioning (Fargen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary compounds present in leaf litter can influence breakdown, as these molecules (e.g. polyphenols or essential oils) have the potential to delay or inhibit fungal growth, impacting microbial colonization and conditioning, and consequently macroinvertebrate attraction (Webster and Benfield 1986;Graça et al 2002;Serra et al 2013). The Novel Weapons Hypothesis (NWH) suggests that secondary compounds produced by exotic species may inhibit native microbes and invertebrates because the native organisms do not share an evolutionary history with the exotic species (Callaway and Ridenour 2004;Bottollier-Curtet et al 2011;Medina-Villar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies comparing litter quality in low-order streams between exotic Rhododendron and native riparian species show similar breakdown rates and similar invertebrate communities (Hladyz et al 2009;Hladyz et al 2011). Serra et al (2013) investigated the impacts of exotic S. fragilis (crack willow) on streams and found that invertebrate abundance and diversity were similar, but species composition differed and the exotic litter decomposed significantly slower than the native litter. In studies investigating the effects of Japanese knotweed on key ecosystem processes in invaded ranges, it has been found that leaf decomposition and macroinvertebrate assemblages were similar between native and non-native leaf species (Braatne et al 2007;Bottollier-Curtet et al 2011).…”
Section: Introductionmentioning
confidence: 99%